Evaluation of Multiple Choice Questions of Oral and Maxillofacial Medicine Courses 1, 2, and 3 in the First Semester of Academic Year 2014-2015 - M Rezai; T Farrokhnia; M Vatanpour; S Lesan; SH Yazdipour (Islamic Azad University, 2018)
Background and aim: Lack of proper assessment of students' knowledge regarding theoretical contents leads to disappointment and negligence by weak students. This study assessed multiple-choice questions (MCQs) of oral and maxillofacial medicine courses in the first semester of the academic year 2014-2015. Materials and Methods: In this cross-sectional study, questions of theoretical oral medicine courses 1, 2, and 3 were assessed according to twelve items in Millman's checklist, including clearness of stem, negative option for stem, specific option, contrastive option, positive words in stem and options, writing structure of stem, duplicated option, the spelling of stem and options, vertically of options, positivity of stem and options, and use of "all of the above" and "none of the above" phrases in options. Difficulty and discrimination coefficients of each question and the rate of compliance with Millman's principles were evaluated using Excel 2007 and SPSS 16. Data were analyzed using descriptive statistics, analysis of variance (ANOVA), and Regression analysis. Results: The responses of 219 students to 113 MCQs were evaluated. In theoretical course 1 with 40 MCQs, discrimination coefficient was 0.36±0.2, difficulty coefficient was 73.2±15.02, and correlation coefficient was 0.58. In theoretical course 2 with 35 MCQs, discrimination coefficient was 0.2±0.04, difficulty coefficient was 70.91±25.13, and correlation coefficient was 0.47. In theoretical course 3 with 38 MCQs, discrimination coefficient was 0.3±0.19, difficulty coefficient was 68.73±26.89, and correlation coefficient was 0.5. The percentage of compliance with Millman's principles was 81.88%, 83.58%, and 84.42% in courses 1, 2, and 3, respectively. Conclusion: The weakest discrimination coefficient was noted in theoretical oral medicine 2. The high percentage of simple difficulty coefficient in the three theoretical courses indicates the necessity of training faculty members in designing questions.